Indices of happiness and unhappiness during treatment of pediatric feeding disorders. (17th January 2022) - Phipps, Laura E.; Peterson, Kathryn M.; Piazza, Cathleen C.
Abstract: To date, there is no research on the measurement of indices of happiness and unhappiness for children receiving behavior‐analytic treatment for feeding disorders and the research on caregiver treatment acceptability during feeding treatment is limited. The purpose of the current study was to measure child indices of happiness and unhappiness during extinction‐based treatment with and without noncontingent reinforcement and to evaluate caregiver treatment acceptability through the course of treatment. Child indices of happiness were idiosyncratic, while indices of unhappiness increased at the onset of treatment and were higher during extinction without noncontingent reinforcement, but eventually decreased. Overall, caregiver treatment acceptability remained high despite temporary increases in emotional responding. The current study introduces measures of social validity to use during feeding treatment (i.e., indices of happiness and unhappiness) and provides evidence that dense schedules of noncontingent reinforcement could serve to mitigate indices of unhappiness during the initial implementation of extinction‐based treatment.